Scandal in scientific reform: the breaking and remaking of science - Bart Penders (Journal of Responsible Innovation)
This perspective explores the Scientific Reform Movement and its links to scandalized claims, such as ‘science is broken’. It delves into the pivotal role of scandal in shaping and sustaining this movement, both rhetorically and politically and portrays scandals as powerful catalysts for change, driving formal requirements for rigor and transparency and giving rise to influential voices like the Center for Open Science. However, there are also potential negative consequences of scandalization, including risking public trust in science and harming careers. This leads to the question of whether reform can occur without the harmful effects of scandalization and ends with a proposal for a need for institutions to adopt a more adaptive and humble character to minimize, but not abandon scandals as a reform strategy.